Types of Plants Used as Nest of Curik Bali in Bali Barat National Park - Arinasa, Ida Bagus Ketut (Proceeding International Conference on Global Resource Conservation, 2013)
Endemic birds of Curik Bali, Jalak Bali or Balinese Starling (Leucopsar rothschildi Stresemann) is very well known throughout the world, but the knowledge of the types of plants used as nest building for reproductive purposes has not been known yet. Natural habitat of Curik Bali is in the forests of Bali Barat National Park. The result showed that there were 16 species from 13 families and 16 genera of plants that are used as nest building for the preparation of breeding. The Fabaceae, Tiliaceae, Euphorbiaceae and Meliaceae families are the most used as nest constituents with two species each. Parts of the plants that are used as nest constituents mostly twigs, leaves, buds and flower parts such as the dried stamens. Beside woody flora and shrubs, grasses are also used as nest constituents. Species characteristic of flora that is used as nest constituents of Curik Bali in Bali Barat National Park will be discussed in this paper.Â Keywords: Flora, Nest, Curik Bali, Bali Barat National Park.